Downregulating Long Non-coding RNAs CTBP1-AS2 Inhibits Colorectal Cancer Development by Modulating the miR-93-5p/TGF-β/SMAD2/3 Pathway - Li, Qiankun; Yue, Wenjing; Li, Ming; Jiang, Zhipeng; Hou, Zehui; Liu, Wei; Ma, Ning; Gan, Wenchang; Li, Yingru; Zhou, Taicheng; Yue, Wenjing; Chen, Shuang (Frontiers in Oncology, 2021)
Background: Colorectal cancer (CRC), the most common malignancy worldwide, has a high mortality rate. In recent decades, long non-coding RNAs (lncRNAs) have been proven to exert an important effect on CRC growth. However, the CTBP1-AS2 expression and function in CRC are largely unknown. Materials and methods: CTBP1-AS2 and miR-93-5p expression in CRC and para-cancerous tissues was detected via reverse transcription-polymerase chain reaction (RT-PCR). The expression of CTBP1-AS2, miR-93-5p and the TGF-β/SMAD2/3 pathway was selectively regulated to study the correlation between CTBP1-AS2 expression and CRC patients' prognosis. CRC cell proliferation, apoptosis and invasion were measured in vivo and in vitro. In addition, bioinformatics was applied to explore the targeting relationship between CTBP1-AS2 and miR-93-5p. The targeting binding sites between CTBP1-AS2 and miR-93-5p, as well as between miR-93-5p and TGF-β, were verified by the dual-luciferase reporter assay and RNA immunoprecipitation experiment. Results: Compared with normal para-cancerous, CTBP1-AS2 was considerably overexpressed in CRC tissues and was closely associated with worse survival of CRC patients. What's more, gain- and loss- experiments illustrated that CTBP1-AS2 accelerated CRC cell proliferation and invasion and inhibited cell apoptosis. Mechanistically, CTBP1-AS2 regulated the malignant phenotype of tumor cells through the TGF-β/SMAD2/3 pathway. Moreover, miR-93-5p, as an endogenous competitive RNA of CTBP1-AS2, attenuated the oncogenic effects mediated by CTBP1-AS2. Conclusion: CTBP1-AS2 promotes the TGF-β/SMAD2/3 pathway activation by inhibiting miR-93-5p, thereby accelerating CRC development.